The condition of proper media education in the family - Nowicka, Ewa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Family has an extremely big impact on child’s development. This is the place where children learn the rules and get to know how to behave correctly. They also gain new experiences and knowledge about the whole world. There, at an early age, the child has the first contact with the world of media. The changes which are introduced into a child’s life and his family by media and multimedia, have positive but also negative aspects. Increasing popularity of media makes a necessity of preparing the youngest users to use them wisely. There is a great role or even a responsibility for their parents. They should show how use the media properly. The way that children will be using new technologies depends on the media education practiced in the family.
Keywords: education; media pedagogy; school; family